ISTILAH DAN MAKNA AKTIVITAS MENGAJI DALAM MASYARAKAT MELAYU DI MEMPAWAH - Farninda Aditya (Jurnal Pendidikan, Kebudayaan dan Keislaman, 2023)
This paper discusses the terms and meanings of Quranic activities in the Malay community of Mempawah, West Kalimantan. The terms used are closely related to traditional Quranic activities to show information on the language used by the local community. The language in the Quranic activities that began to fade in use in the community due to the number of traditional teachers who are the parents of local language actors have died and the shift to more modern Quranic learning activities. The purpose of this paper is to record the term and meaning of Quranic activity as a Malay language document in Mempawah. This research is Qualitative with Sociolinguistic approach and interview collection technique, data provision, data analysis with literature review technique. This research resulted in 30 terms and meanings sourced from language sources; Indonesian, Malay, and Arabic as well as local languages whose sources are unknown. Terms and Meanings in Activities have similar meanings but different sounds by experiencing changes in sound and origin of language sources. The terms and meanings are related to; Equipment, Attitude, Petuah, and Level of Ability in Mempawah Malay Community's Quranic Activity.